2019
DOI: 10.1097/mao.0000000000002340
|View full text |Cite
|
Sign up to set email alerts
|

A Transcutaneous Active Middle Ear Implant (AMEI) in Children and Adolescents: Long-term, Multicenter Results

Abstract: Objective: Evaluation of the long-term safety and performance of an active middle ear implant (AMEI) in the treatment of hearing loss in children and adolescents with a primary focus on improvement in speech discrimination. Study Design: Prospective, multicentric, single-subject repeated-measures design in which each subject serves as his or her own control. Subjects: Thirty-one pediatric subjects aged 5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
2
7
0
4
Order By: Relevance
“…A recent multi-center study showed that the VSB is a safe and feasible device for children and adolescents with aural atresia, and can provide stable audiological performance in the long run. 31 Both the BB and the VSB have provided safety and excellent hearing benefit for patients with atresia. It is still not easy to choose which implantation method for patient with unilateral malformation will be the best.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-center study showed that the VSB is a safe and feasible device for children and adolescents with aural atresia, and can provide stable audiological performance in the long run. 31 Both the BB and the VSB have provided safety and excellent hearing benefit for patients with atresia. It is still not easy to choose which implantation method for patient with unilateral malformation will be the best.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction and performance of the Soundbridge have been high and consistent across centres, countries, and continents [22][23][24][25][26][27]. In general, patients who wear the device all day (up to 16 h), report a natural sound quality, high device satisfaction, and a better ability to understand speech, especially in noisy environments [21].…”
Section: Vibrant Soundbridge -The Devicementioning
confidence: 98%
“…In drei klinischen Studien wurde das Sprachverstehen mithilfe von alltagssimulierenden Satztests mit festem Störgeräuschpegel und adaptiven Sprachschallpegel (Oldenburger Satztest oder Oldenburger Kindersatztest) bewertet. Mit einer Verbesserung der SNR um 4–6 dB konnte auch hier der positive Versorgungseffekt bestätigt werden 99 101 104 .…”
Section: Ergebnisseunclassified
“…5). Due to the low incidence of such malformations that amounts to 1:3,300-1:10,000 [94,95], the numbers of cases in clinical trials that focus on audiological outcomes after VSB implantation in children are often very low [96][97][98][99][100][101][102][103][104]. All currently available clinical trials (▶Table 6) could confirm a satisfactory speech recognition score in quiet of 80-100 % at 65 dB SPL.…”
Section: Active Middle Ear Implants In Pediatric Audiologymentioning
confidence: 99%
See 1 more Smart Citation